Single Parent Parenting in Developing Social Emotional of 4-5 Years Old Children - Huda, Firtia Husnul; Dea, Leli Fertiliana; Utama, Ferdian (Bulletin of Early Childhood, 2023)
Social emotional development is one of the important aspects of development that must be prioritized in learning in early childhood. The formulation of the problem in this study is How is single parent parenting in developing the social-emotional development of children aged 4-5 years at RA Bustanul 'Ulum Jayasakti Kec. Anak Tuha, Kab. Lampung Tengah? This study aims to explore and analyze single parent parenting patterns and their impact on the social emotional development of children aged 4-5 years at RA Bustanul 'Ulum Jayasakti. Using a qualitative approach through in-depth interviews with single parents and observations of children's behavior, this study attempts to describe the variations of parenting patterns applied and identify the developmental characteristics of children from this group. The results of the study highlighted the complexity of single-parent parenting that has an impact on the diverse social-emotional characters of children. The findings show that children from single parent families exhibit varied characteristics, such as different levels of independence, adaptability to the social environment, and responses to educational stimuli. Thus, this study not only makes a theoretical contribution to the literature on parenting and child development, but also has a significant practical impact in the context of early childhood education and care from single parent families. Keywords: Parenting, Single Parent, Social Emotional